Weather and climate. - Polgreen, John (New York, Random House, 1969)
Describes the structure of the atmosphere and the many forces that act upon it to create a great variety of climates and weather. Gives a brief explanation of how to forecast weather.
Keywords: Weather -- Juvenile literature; Climatology -- Juvenile literature; Weather; Climatology